Expresamos nuestros sentimientos a través de recursos no verbales - Olortiga Torres, Liz Daysi (2020)
In the present work of professional sufficiency, the learning session is developed with his sustenance the scientist - philosophical and psychopedagogical._x000D_ The topic of Communication, Non-verbal Communication and non-verbal resources is addressed on the scientific-philosophical basis._x000D_ On the psychopedagogical basis we reach the psychological and pedagogical bases that allow us to develop the learning session to achieve in students the development of their scientific competences.